Pressure gauge accuracy and tire maintenance awareness among vehicle owners in Birnin Kebbi, Nigeria - Ademola James Adeyemi; Olusegun Isa Lasisi; Abubakar Arzika Zaki; Sani Isa Besse; Muhammad Bello Ambursa (Universitas Serang Raya, 2020)
Aside from human factors, tire blowouts and other tire imperfections are major contributors to the persistently high road accident rate. While tire imperfections are categorized as part of the mechanical factors affecting road accident, the tire maintenance personnel and the vehicle owners' human behavior plays a significant role in ensuring that accidents due to tire imperfections are minimized. Therefore, this study aims to determine the accuracy of the pressure gauges used by tire maintenance personnel, popularly called vulcanizers in Nigeria, and to determine the level of awareness of vehicle owners about the basic information that affects the safe use of tires on the road. The study consists of two stages. The first stage investigates the accuracy of the pressure gauges used by twenty vulcanizers in four different districts in Birnin Kebbi, the northwestern part of Nigeria. The second stage was an online survey regarding the tire maintenance behavior of 87 participants, who were formally educated from Diploma to Ph.D. level. The study's findings showed that about 25% of the vulcanizers do not use pressure gauges to measure air pressure during tire inflation, and less than 17% of the readings taken were accurate. Yet about 60% of the respondents believe that vulcanizers' pressure gauges are reliable and less than 30% of the respondents know that the expiring date of tires is four years in Nigeria. Therefore, there is an urgent need for proper awareness about tire usage and maintenance among the general population. It would also be appropriate to include such basic road safety information in the school curriculum at all levels.